Gluten-free girl and the chef : a love story with 100 tempting recipes - Ahern, Shauna James; Ahern, Daniel, 1968- (Hoboken, N.J. : John Wiley, 2010)
'When she was diagnosed with celiac disease, Shauna set out to discover and delight in the best food she could eat. Then she met Daniel, a talented chef who had spent his career cooking at great restaurants across the country. They fell in love at the grocery store, the farmers' market, and in front of the stove. Soon Daniel was creating spectacular dishes, stunning meals that happened to be entirely gluten-free'--Cover, p. 2
Keywords: Gluten-free diet -- Recipes; Celiac disease -- Patients -- United States; Gluten-free diet; Gluten-free foods; Cookbooks